Alterations in bone marrow microRNA expression profiles on infection with avian pathogenic Escherichia coli. (5th December 2022) - Yin, Lei; Shen, Xuehuai; Zhang, Danjun; Zhao, Ruihong; Hou, Hongyan; Hu, Xiaomiao; Wang, Jieru; Dai, Yin; Pan, Xiaocheng; Qi, Kezong
Abstract: Avian pathogenic Escherichia coli (APEC) is one of the most common avian bacterial diseases globally. The bone marrow is a reservoir of immature immune cells. To elucidate the role of bone marrow microRNAs (miRNAs) in regulating the host response to APEC infection, we performed miRNA-seq to investigate alterations in the expression of bone marrow miRNAs in three groups of specific pathogen-free chickens: non-challenged (NC) and challenged with APEC for 12 h (C12) and 24 h (C24). Twenty and 19 differentially expressed miRNAs (fold change >2, P  < 0.01) were identified on comparing the NC and C12 and the NC and C24 groups, respectively. On functional annotation analysis of target genes of differentially expressed miRNAs, we found that the gene ontology term "immune system process" was significantly enriched at both 12 h and 24 h; moreover, several important signaling pathways were triggered in response to APEC infection, such as MAPK, cGMP-PKG, Notch, and cAMP pathways. In addition, we performed reverse transcription quantitative real-time PCR (qRT-PCR) to validate the differential expression of miRNAs. qRT-PCR data were similar to the sequencing data. On constructing an miRNA–target gene network, gga-miR-2127, gga-miR-6643-5p, and gga-miR-6567-3p were found to potentially play a vital role in the immune process. Overall, our findings provide deeper insights into miRNA transcriptome changes involved in the immune response of the chicken bone marrow to APEC infection. Highlights: Mechanism underlying bone marrow immune response to APEC infection was elucidated. Many miRNAs were differentially expressed after APEC infection for 12 h and 24 h. The GO term "immune system process" was significantly enriched at both timepoints. APEC infection triggered MAPK, cGMP-PKG, cAMP, and Notch signaling pathways. gga-miR-2127, gga-miR-6567-3p, and gga-miR-6643-5p are key during APEC infection.